Analisis Kesulitan Menyelesaikan Soal Cerita Matematika Pada Siswa Kelas IV SDN Mekarjaya 14 - Fitria Meliana Sari; Dwi Fitricia Cahyaningrum; Bahesti Zahra (Bilangan : Jurnal Ilmiah Matematika, Kebumian dan Angkasa, 2024)
This research aims to analyze the difficulties of fourth grade students at SDN Mekarjaya 14 in solving mathematics story problems. This research uses qualitative research with an inductive method. This research aims to gain knowledge based on correct and reliable data and facts about students' mathematics learning difficulties in the form of story problems. The research instrument used was observation of test questions in the form of stories. The technique for checking the validity of the data is using triangulation. Based on the results of observations, there were still many respondents who made mistakes in working on the questions, including mistakes in changing story questions into mathematical sentences and using arithmetic operations. In general, students have difficulty working on story problems which are presented in the form of story problems. Apart from that, respondents also did not master multiplying results up to 100. In accordance with findings in the field, it can be concluded that there were difficulties experienced by respondents, including difficulties in understanding concepts and material,master and use arithmetic operations, for example multiplication and division. Meanwhile, the factors that caused respondents to experience difficulty learning mixed arithmetic operations included their lack of mastery of the concepts of multiplication and division, and the lack of time provided by respondents to repeat lessons at home.